2013
DOI: 10.1242/dmm.010348
|View full text |Cite
|
Sign up to set email alerts
|

Cell culture andDrosophilamodel systems define three classes of anaplastic lymphoma kinase mutations in neuroblastoma

Abstract: SUMMARYNeuroblastoma is a childhood extracranial solid tumour that is associated with a number of genetic changes. Included in these genetic alterations are mutations in the kinase domain of the anaplastic lymphoma kinase (ALK) receptor tyrosine kinase (RTK), which have been found in both somatic and familial neuroblastoma. In order to treat patients accordingly requires characterisation of these mutations in terms of their response to ALK tyrosine kinase inhibitors (TKIs). Here, we report the identification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 39 publications
4
74
0
Order By: Relevance
“…However, brigatinib inhibits ALK addicted neuroblastoma cell line proliferation with roughly 2 to 3-fold lower IC 50 values compared with crizotinib. Previously described expression of gain-of-function "hot spot" ALK mutations ALK-F1174L and ALK-R1275Q in Drosophila eye imaginal discs with the Gal4-UAS-system results in a rough eye phenotype that is 100% penetrant [7,38,40]. Offspring that were grown on food containing brigatinib displayed a concentration dependent improvement of the rough eye phenotype.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, brigatinib inhibits ALK addicted neuroblastoma cell line proliferation with roughly 2 to 3-fold lower IC 50 values compared with crizotinib. Previously described expression of gain-of-function "hot spot" ALK mutations ALK-F1174L and ALK-R1275Q in Drosophila eye imaginal discs with the Gal4-UAS-system results in a rough eye phenotype that is 100% penetrant [7,38,40]. Offspring that were grown on food containing brigatinib displayed a concentration dependent improvement of the rough eye phenotype.…”
Section: Discussionmentioning
confidence: 98%
“…The expression of human ALK proteins was confirmed by immunostaining of eye discs using antihuman ALK antibody ( Supplementary Figure 2A, 2B). Ectopic expression of the ALK gain-of-function alleles F1174L and R1275Q led to disrupted eye morphology in all offspring (100%), a so called 'rough eye' phenotype, which is characterized by disorganized ommatidia and missing interommatidial bristles, reflecting their robust ligand-independent activity ( Figure 3) [7,38,40]. All larvae that were grown on brigatinib inhibitor-containing food developed into flies which showed a concentrationdependent improvement of the rough eye phenotype (Figure 3).…”
Section: Brigatinib Blocks Activity Of the Alk Gain-offunction Allelementioning
confidence: 99%
See 1 more Smart Citation
“…The F1174 residue lies in the alpha C helix [3] and it has been suggested that a F to L change will result in an increased affinity for ATP [20]. The F1174L mutation has been shown to be a ligand-independent activating mutation [21]. The L and V residues present with the same physicochemical properties and are expected to induce the same consequences on the receptor's activity.…”
Section: Discussionmentioning
confidence: 99%
“…It was also proven that ALK antagonists, such as crizotinib, may effectively block neurite outgrowth in a ligand-independent manner. They also decreased the activity of all types of mutant ALK receptors, thus inhibiting the ALKdependent signal transduction pathways [119]. The response to the inhibitors depends on the dose and the type of ALK mutation, with F1774L being the most resistant to the drug and with complete regression of the xenograft in cases with ALK amplification or R1275Q mutation [120].…”
Section: • • Neuroblastomamentioning
confidence: 99%